Health effects of air quality regulations in Delhi, India - Foster, Andrew; Kumar, Naresh (Atmospheric environment (1994), 2011)
This, the first systematic study, quantifies the health effects of air quality regulations in Delhi, which adopted radical measures to improve air quality, including, for example, the conversion of all commercial vehicles to compressed natural gas (CNG), and the closure of polluting industries in residential areas from 2000 to 2002. Air pollution data, collected at 113 sites (spread across Delhi and its neighboring areas) from July–December 2003, were used to compute exposure at the place of residence of 3989 subjects. A socio-economic and respiratory health survey was administered in 1576 households. This survey collected time-use, residence histories, demographic information, and direct measurements of lung function with subjects. The optimal interpolation methods were used to link air pollution and respiratory health data at the place of their residence. Resident histories, in combination with secondary data, were used to impute cumulative exposure prior to the air-quality interventions, and the effects of recent air quality measures on lung function were then evaluated. Three important findings emerge from the analysis. First, the interventions were associated with a significant improvement in respiratory health. Second, the effect of these interventions varied significantly by gender and income. Third, consistent with a causal interpretation of these results, effects were the strongest among those individuals who spend a disproportionate share of their time out-of-doors. ► The study examines health effects of air quality regulations in Delhi. ► Environmental regulations in Delhi improved air quality. ► A novel methodology to compute personal exposure. ► Time-activity diary and residential history were used to compute exposure. ► Improvement in air quality show a significant improvement in respiratory health.